LOW-COST REAL-TIME ELECTROMYOGRAPHY (EMG) DATA ACQUISITION EXPERIMENTAL SETUP FOR BIOMEDICAL TECHNOLOGIES EDUCATION - MULAYİM, Naciye and CİKLACANDİR, Samet and CAN, Fatih Cemal and SAHİN, Savas (The Eurasia Proceedings of Educational and Social Sciences, 2017)
Electromyography (EMG) is a technique used in electro-diagnostic therapy by recording and evaluating the skeletal muscle electrical activity. When muscle cells are activated, electric potential, which is produced by these cells, is detected via an electromyography. These signals can be use analyzing of medical activation levels, anomalies and detection of recruitment order. At the same time they can used to make analyses of biomechanics motions of human or animals. In this study, it was developed a real time EMG data acquisition system based on threshold level. Firstly, it was generated an EMG sensor and it was obtained EMG signals by communication between Arduino and LabVIEW interface by using muscle electrodes. It was purposed to use for developing of a low-cost real-time application in laboratory for biomedical technologies education.